Student Awards Luncheon - (:unkn) unknown (My University, 2016)
This is a recording of the Student Awards Luncheon from the 2016 Research and Creative Achievement Week. The presentation features the following awards: RCAW Awards; Thesis/Dissertation Awards; ECU Distinguished Graduate Faculty Mentor Awards; Carol F. Volkman Awards; Coastal Scholars Awards.
Keywords: RCAW; Awards; Student awards; Faculty awards